"Spontaneous Twiddler's" Syndrome: The Importance of the Device Shape. Issue 3 (26th December 2016) - GUL, ENES E.; BOLES, USAMA; HASEEB, SOHAIB; GLOVER, BENEDICT; SIMPSON, CHRIS; BARANCHUK, ADRIAN; MICHAEL, KEVIN
Abstract : Twiddler's syndrome is caused by patient manipulation of the cardiac implantable device (CID) around its central axis within the pocket, resulting in retraction and dislocation of the electrodes. There are, however, some reports that Twiddler's syndrome may occur spontaneously without the patient's manipulation. This remains contentious as it may be argued that patients may not want to admit to manipulating the CID or may have been unaware of their actions. Recently, we have observed three very similar cases with a "spontaneous" Twiddler's syndrome resulting in lead displacement. All of the three patients denied device manipulation and were not prone to somnambulism or repetitive involuntary motor behaviors. It, therefore, seems highly unlikely that all patients could have manipulated the device in exactly the same way to result in the same postrotational position within the implant pocket. The fact is that the same device was implicated in all these cases in a relatively similar time sequence from implant to recognition of the implantable cardiac defibrillator rotation. We postulate that the unique elongated decision of the Fortify Assura (St. Jude Medical, Minneapolis, MN, USA) ICD makes this device prone to spontaneous rotation as is exemplified by our case series.